Opioid use disorder incidence and treatment among incarcerated pregnant women in the United States: results from a national surveillance study. (18th March 2020) - Sufrin, Carolyn; Sutherland, Lauren; Beal, Lauren; Terplan, Mishka; Latkin, Carl; Clarke, Jennifer G.
Abstract: Background and Aims: The established standard care in pregnancy is medication for opioid use disorder (MOUD); however, many institutions of incarceration do not have MOUD available. We aimed to describe the number of incarcerated pregnant women with opioid use disorder (OUD) in the United States and jails' and prisons' MOUD in pregnancy policies. Design: Epidemiological surveillance study of 6 months of outcomes of pregnant, incarcerated women with OUD and cross‐sectional survey of institutional policies. Setting: United States. Participants: Twenty‐two state prison systems and six county jails. Measurements: The number of pregnant women with OUD admitted and treated with methadone, buprenorphine or withdrawal; policies on provision of MOUD and withdrawal in pregnancy. Findings: Twenty‐six per cent of pregnant women admitted to prisons and 14% to jails had OUD. One‐third were managed through withdrawal. The majority who were prescribed MOUD were on methadone (78%, prisons; 81%, jails), not buprenorphine. While most sites ( n  = 18 prisons, n  = four jails) continued pre‐incarceration MOUD in pregnancy, very few initiated in custody ( n  = four prisons; n  = two jails). Two‐thirds of prisons and three‐quarters of jails providing MOUD in pregnancy discontinued it postpartum. Conclusions: In this sample of US prisons and jails, one‐third required pregnant women with opioid use disorder to go through withdrawal, contrary to medical guidelines. More women were prescribed methadone than buprenorphine, despite the fewer regulatory barriers on prescribing buprenorphine. Most sites stopped medication for opioid use disorder postpartum, signaling prioritization of the fetus, not the mother. Pregnant incarcerated women with opioid use disorder in the United States frequently appear to be denied essential medications and receive substandard medical care.